ACTIVE CYCLE OF BREATHING TECHNIQUE FOR AIRWAY CLEARANCE AND RESPIRATORY FUNCTION IN PULMONARY TUBERCULOSIS: A CASE STUDY - Ramadhan, Sukma Cahya; Ainiyah, Nur (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: Pulmonary tuberculosis (TB) remains a major public health challenge in Indonesia, often leading to ineffective airway clearance due to excessive secretions. Non-pharmacological interventions, such as chest physiotherapy and deep breathing, are widely used; however, their effectiveness can be further enhanced through the Active Cycle of Breathing Technique (ACBT). Objectives: This study aimed to describe the nursing care process using ACBT and evaluate its effectiveness in improving airway clearance and respiratory function in a patient with pulmonary TB. Methods: A single-case descriptive study using an evidence-based nursing approach was conducted with an 82-year-old female patient diagnosed with pulmonary TB and ineffective airway clearance. ACBT was administered once daily for four consecutive days, each session lasting 15 minutes. Data were collected through observation, clinical documentation, and semi-structured interviews, and analyzed descriptively by comparing pre- and post-intervention respiratory parameters (respiratory rate, oxygen saturation, sputum characteristics, and lung sounds). Results: Clinical indicators showed progressive improvement. Respiratory rate decreased from 24 to 20 breaths/min, oxygen saturation increased to 97% on room air, and auscultation revealed reduced wheezing and rhonchi. The patient reported easier sputum expectoration and reduced dyspnea after four days of intervention. Conclusion: ACBT effectively enhanced airway clearance and respiratory function in a pulmonary TB patient. It is recommended as an evidence-based, non-pharmacological intervention for respiratory nursing practice.